Pembelajaran Matematika Sebagai Media Pendidikan Karakter - Yuliandari, Ria Norfika (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2017)
Character building recently has become a national issue that piques many people’s interests. Character building is all about an effort to develop positive characters in students. Character building is relevant to develop students’ positive character values in formal education. The development of students’ positive character values in formal education will succeed if there is integration between the character values and themes or topics of discussion in every subject. Mathematics, as one of the most time-consuming subjects learned at school, has to be able to be designed as a media presenting the character values in character building. As a result, Mathematics will not always only emphasize on cognitive aspects, but also build positive character values. The character values included in Mathematics’ learning objectives are honesty, discipline, curiosity, hard work, responsibility, creative, independence and communicativeness. To conduct Mathematic learning with the character values, there has to be compatibility among Mathematics’ learning objectives, competency as written in the curricula, and the character building values.